Exploring the Contributing Factors to Irregular Migration Towards Sweden Among Eritreans in Egypt - Alhasn, Mohammad Ammar (AUC Knowledge Fountain, 2025)
This thesis provides an understanding of the interplay between individual aspirations, social networks, and policy frameworks to explore the impact of such factors on the mobility of Eritreans from Egypt towards Sweden. Utilizing a qualitative research approach, the study engaged with twenty-four Eritreans through semi-structured interviews to delve into their lived experiences and decision-making processes. The research is underpinned by theoretical frameworks as follows: social network theory, and institutional theory, which collectively inform the analysis of the migratory phenomenon. The findings reveal that the decision to undertake irregular migration is driven by a confluence of factors in Egypt as a country of first asylum. Among these factors are the pursuit of safety, human rights, and improved living standards, which are perceived to be lacking in Egypt. Eritreans in Egypt face significant challenges including discrimination, limited access to essential services, and economic instability, which contribute to their decision to leave. Social networks emerge as pivotal in shaping migration decisions, providing information, financial support, and guidance, while also facilitating connections with smugglers. Policies and procedures in Sweden impact Eritrean migrants by offering varying degrees of protection and integration opportunities, influencing their choice of destination.